Do Fish Drive Recreational Fishing License Sales?. (3rd January 2017) - Hunt, Len M.; Bannister, Allison E.; Drake, D. Andrew R.; Fera, Shannon A.; Johnson, Timothy B.
Abstract: Management agencies need to understand the factors that influence fishing license purchases. While traits such as gender can influence the decisions of recreational fishers, a gap remains in understanding the influence of catch‐related fishing quality on these decisions. We evaluated the use of fish biomass density as a proxy for catch‐related fishing quality along with non‐catch‐related factors (population density, gender, and ethnicity) to explain variation in 2014 resident fishing license rates across 510 origins in Ontario. License rates were higher in areas with lower population density (i.e., rural areas), in areas with higher fish biomass density, and among populations with stronger representation by ethnic majorities. From simulated scenarios, we predicted that resident license sales could increase between 14% and 25% if fish biomass density increased by 30% and 54% in northeastern and southern Ontario, respectively. However, license sales could decrease between 5% and 10% with a 30% redistribution of rural residents to a major urban area. The relationship between license rates and non‐catch‐related factors confirms the role of urbanization on recreational fishing participation, while catch‐related factors provide support for a functional response by fishers to fish. Received April 28, 2016; accepted October 3, 2016Published online January 3, 2017